Electric-Field-Driven Generative Nanoimprinting for Tilted Metasurface Nanostructures - Fan, Yu; Wang, Chunhui; Tian, Hongmiao; Chen, Xiaoming; Li, Ben Q.; Wang, Zhaomin; Li, Xiangming; Chen, Xiaoliang; Shao, Jinyou (Nano-Micro Letters, 2025)
Tilted metasurface nanostructures, with excellent physical properties and enormous application potential, pose an urgent need for manufacturing methods. Here, electric-field-driven generative-nanoimprinting technique is proposed. The electric field applied between the template and the substrate drives the contact, tilting, filling, and holding processes. By accurately controlling the introduced included angle between the flexible template and the substrate, tilted nanostructures with a controllable angle are imprinted onto the substrate, although they are vertical on the template. By flexibly adjusting the electric field intensity and the included angle, large-area uniform-tilted, gradient-tilted, and high-angle-tilted nanostructures are fabricated. In contrast to traditional replication, the morphology of the nanoimprinting structure is extended to customized control. This work provides a cost-effective, efficient, and versatile technology for the fabrication of various large-area tilted metasurface structures. As an illustration, a tilted nanograting with a high coupling efficiency is fabricated and integrated into augmented reality displays, demonstrating superior imaging quality. Highlights: 1 The developed electric-field-driven generative-nanoimprinting technology enables direct fabrication of large-area tilted metasurface nanostructures with cost-efficiency and high-throughput advantages. 2 Real-time tuning of process parameters facilitates customized fabrication of various tilted metasurface nanostructures. 3 Integration of these custom-designed high-angle-tilted nanostructures into augmented reality displays achieves superior image quality.